180‐degree immersive VR motion visualization in the treatment of haemophilic ankle arthropathy. Issue 1 (19th October 2022) - Ucero‐Lozano, Roberto; Pérez‐Llanes, Raúl; López‐Pina, José Antonio; Cuesta‐Barriuso, Rubén
Abstract: Background: Patients with haemophilic arthropathy suffer chronic pain that affects and restricts their quality of life. Visualization of movement through immersive virtual reality is used for pain management. Aim: To evaluate the efficacy of 180‐degree immersive VR motion visualization therapy in patients with haemophilic ankle arthropathy. Methods: Prospective, multicentre pilot study. Fifteen adult patients with bilateral haemophilic ankle arthropathy were recruited (mean age: 42.73 ± 12.36 years). The intervention lasted 4 weeks, with daily home sessions of 180‐degree immersive motion visualization. The patients were given virtual reality glasses to use with their smartphones. From the YouTube mobile app® they accessed the recorded video with access from the He‐Mirror App®. The study variables were joint state (Haemophilia Joint Health Score), pressure pain threshold (pressure algometer), muscle strength (dynamometry) and range of motion (goniometry). Three evaluations were performed: at baseline (T0), after the intervention (T1) and at the end of a 16‐week follow‐up period (T2). Results: No patient developed ankle hemarthrosis during the experimental phase. In the repeated measures analysis we found statistically significant differences in joint state (F = 51.38; η 2 p = .63), pressure pain threshold of the lateral malleolus (F = 12.34; η 2 p = .29) and range of motion (F = 11.7; η 2 p = .28). Conclusions: Therapy using immersive motion visualization does not cause hemarthrosis. This intervention can improve joint condition, pressure pain threshold and range of motion in patients with ankle arthropathy. Changes greater than the MDC were reported in more than 40% of patients for the variables pressure pain threshold, anterior tibialis strength and range of motion, which were considered clinically relevant.